2010
DOI: 10.1007/s11676-010-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of coconut tree leaf sheath fiber reinforcement

Abstract: The coconut palm tree leaf sheath fibers were analyzed by FTIR spectral analysis, Chemical, X-ray and thermo gravimetric methods to assess their suitability as reinforcements in the preparation of green composites. The morphology of the untreated and alkali treated fibers was studied by scanning electron microscopic method. The FTIR and chemical analyses indicated lowering of hemi-cellulose content by alkali treatment of the fibers. The X-ray diffraction revealed an increase in crystallinity of the fibers on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 23 publications
5
45
0
1
Order By: Relevance
“…24 The vibration peak at 2924 cm À1 , corresponding to the stretching of the C-H aliphatic group was included in almost all natural fibres. 4,23,24 The intensity of this peak decreased due to the removal of hemicelluloses, which agreed with the results reported by Hossain et al 23 and Ouajai et al 24 In addition, the band observed at 1734 cm À1 was assigned to C ¼ O stretching vibration of the carboxylic acid and ester compounds of hemicelluloses and lignin. 24 The intensity of this peak also weakened after alkali treatment.…”
Section: Mechanical Testssupporting
confidence: 90%
See 1 more Smart Citation
“…24 The vibration peak at 2924 cm À1 , corresponding to the stretching of the C-H aliphatic group was included in almost all natural fibres. 4,23,24 The intensity of this peak decreased due to the removal of hemicelluloses, which agreed with the results reported by Hossain et al 23 and Ouajai et al 24 In addition, the band observed at 1734 cm À1 was assigned to C ¼ O stretching vibration of the carboxylic acid and ester compounds of hemicelluloses and lignin. 24 The intensity of this peak also weakened after alkali treatment.…”
Section: Mechanical Testssupporting
confidence: 90%
“…The advantages of natural fibre composites are their renewability, environmental compatibility, low cost, low density, flexibility of use and biodegradability. [1][2][3][4][5][6][7][8] In addition, plant fibres generate less health problems than mineral fibres when used as a reinforcing agent in polymer composites. 9 Nevertheless, some drawbacks can be encountered in their use: (i) mainly the poor interfacial adhesion between the fibre of hydrophilic nature and the hydrophobic polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The coir fibre derived from its seed husk is well-known and used in floor coverings, mattress fillings and others. Among other fibres found on a coconut palm [105], the layers of fibrous sheets in the leaf-sheath (base of the leaf stalk attached to the tree trunk) with fibres in the alternating sheets oriented nearly orthogonal to each other appear to be already in a woven structure [106]. Interestingly, the leafsheath consists of three distinct types of multicellular fibres made of mostly cellulose and lignin arranged in a highly ordered structure.…”
Section: Diverse Use Of Fibresmentioning
confidence: 99%
“…Most of the drawbacks can be overcome by using natural fibers in the place of synthetic fibers. The usage of naturally available products (fibers, agriculture wastes and wood) as reinforcement in green composites has been increased enormously, because of its biodegradable character, economical and high abundance in availability availability (N. C. Sandeep et al 2017; Reddy et al 2010;Thakur et al 2010;Wambua et al 2003). Poor compatibility between fiber and matrix has been one of the main problems ran across in using the natural fibers in composites (Singha and Rana 2012).…”
Section: Introductionmentioning
confidence: 99%